The effect of the grooved elastic damping component in reducing friction-induced vibration. (June 2017) - Wang, D.W.; Mo, J.L.; Zhang, Q.; Zhao, J.; Ouyang, H.; Zhou, Z.R.
Abstract: In this work, the effect of the grooved elastic damping component on the friction-induced vibration is investigated by using both experimental and numerical analysis. Experimental results show that the Styrene Butadiene Rubber (SBR) with grooves on its surface can reduce the vibration level, suppress the generation of vibration frequency and alleviate the effect of disc surface run-out. To reveal the role of the grooves in modifying friction-induced vibration, three SBR components with grooves distributed on three different regions are tested. The results show the grooves in the middle region can reduce the vibration amplitude, while the grooves in both the leading and trailing regions can eliminate higher vibration frequency. Numerical analysis is performed to provide reasonable explanations on experimental phenomenon. Highlights: The effect of grooved damping samples on friction-induced vibration is studied. Damping samples with three kinds of groove configurations are tested. How the different regions' grooves affect friction-induced vibration are discussed. Numerical analysis is carried out to explain the experimental phenomenon.